Neurodevelopmental justice: rethinking adolescent criminal responsibility in Puerto Rico - Ramírez-Rivera, Edicer; Martínez-González, Karen G. (Frontiers in Psychology, 2026)
Developmental neuroscience has increasingly informed debates about adolescent criminal responsibility by highlighting ongoing maturation of cognitive control, emotional regulation, and decision-making systems during adolescence. This Perspective examines how neuroscientific findings have been interpreted within legal and policy discussions of juvenile culpability, using Puerto Rico’s distinctive juvenile justice framework as a focal context. Rather than treating neurodevelopment as a causal explanation for criminal behavior, the article situates brain development within broader social, environmental, and legal conditions that shape adolescent conduct. Drawing on neuroscientific research, comparative legal analysis, and empirical evidence on justice-system outcomes, the article examines how concepts such as graduated responsibility, proportional accountability, and adolescents’ capacity for change align with Puerto Rico’s developmentally oriented juvenile justice model. Empirical evaluations of juvenile transfer policies are incorporated to assess public-safety, health, and developmental outcomes associated with adult-court prosecution versus juvenile-system processing. The discussion highlights both the promise and the limits of applying neuroscience to legal decision-making, emphasizing the importance of avoiding deterministic interpretations while recognizing adolescents’ heightened responsiveness to intervention and rehabilitation. The article argues that developmentally informed juvenile justice should prioritize fairness, contextualized responsibility, and access to trauma-informed, evidence-based supports. It also underscores the importance of interdisciplinary dialog and regionally grounded research for juvenile justice policy and practice in Puerto Rico.